STRATEGI KOMUNIKASI PARIWISATA DINAS PARIWISATA PALEMBANG DALAM MENINGKATKAN MINAT WISATAWAN KE KOTA PALEMBANG - Riko Fardiansyah (Jurnal Ilmu Komunikasi Balayudha, 2025)
Abstract This research was conducted to determine the tourism communication strategy of the Palembang City Tourism Office in increasing tourism interest in the city of Palembang. This research uses qualitative methods which aim to describe situations or phenomena. This research is a combination of primary data and secondary data. Data collection techniques using observation, interviews and documentation. Data analysis, namely data reduction, data presentation, and drawing conclusions. The research results show that the parties involved in developing tourist objects have implemented tourism communication strategies, but they are not yet optimal. In tourism communication, to seek interest in traveling, a communication strategy is used. The choice of communication strategy must be done very carefully. Mistakes in determining strategy can cause various losses, especially in terms of time, costs and resources. Tourism communication strategies focus, among other things, on: images, natural attractions, community support and advances in information technology. Tourism communication strategies that always highlight natural and cultural attractions as well as the friendliness of our people.   Keywords: Strategy Communication,Tourist, information,